2016
DOI: 10.1177/0021909614552917
|View full text |Cite
|
Sign up to set email alerts
|

Crime statistics in a Nigerian Traditional City: A Geographic Analysis

Abstract: The study identified predominant crime type and pattern of crime occurrence in Ile-Ife, Nigeria. The research used crime data, by type and location, from January 2005 to December 2010. The spatial distribution of crime types revealed that 68 cases (49%) of offences against individuals occurred in the core area of the city, 40 (29%) in the transition area and 31 (22%) in the suburban, while 184 (20%), 265 (30%) and 451 cases (50%) of offences against property occurred in the core, transition and suburban respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
4
7
0
Order By: Relevance
“…The study supports the finding of Afon (2001) that criminal activities are more prevalent in certain densities with different degrees of incidence. This finding also corroborates the study of Abodunrin (2004), Adigun (2012), Badiora et al (2013), andBadiora et al (2014). The reason for this variation may be attributed to differences in socioeconomic characteristics of the residents and the environmental characteristics of the residential area in the study area…”
Section: Level Of Crime Occurrences In the Three Residential Areas In...supporting
confidence: 91%
See 1 more Smart Citation
“…The study supports the finding of Afon (2001) that criminal activities are more prevalent in certain densities with different degrees of incidence. This finding also corroborates the study of Abodunrin (2004), Adigun (2012), Badiora et al (2013), andBadiora et al (2014). The reason for this variation may be attributed to differences in socioeconomic characteristics of the residents and the environmental characteristics of the residential area in the study area…”
Section: Level Of Crime Occurrences In the Three Residential Areas In...supporting
confidence: 91%
“…Rader (2017) also corroborated that perceptions of crime have increased while the crime rate decreases most times. Studies in developing countries have shown a relationship between the two (Quang& Hang, 2002;Tseloni & Zarafoniton, 2008;Badiora et al, 2014). An increase in crime waves often increases the fear of crime among people in the cities of developing countries especially Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…It also observed that more crime fatalities are in the southern part of Nigeria than in the north, because Lagos, Rivers, Ogun and Imo states in the south were reported as the most affected crime states. Badiora and Afon (2013), Badiora (2014); and Badiora et al (2016) examined the predominant crime type and pattern of occurrence in Ile-Ife, Nigeria. The study classified the study area into the core area, the transition zone and the suburban areas.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Similarly, the interaction of physical and sociocultural environment influences human behavior and propensity to engage in crime; for instance, an environment with poor illumination and bushy abandoned properties will create a suitable abode harboring criminals (Ball et al, 2001;Ogboi and Eze, 2013). Badiora et al (2016) investigated crime variation spatially in the core, transition and suburban; the study reported disparities in the nature and occurrence of crime across the zones with varying consequences. Consequences of crime occurrence on victims are numerous depending on the object of attack (human, properties and morality) (Graif et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that variations exist in the numbers of reported crimes across different landuse types, housing densities and rural-urban divides (Fajnzylber et al, 2000;Fafchamps and Moser, 2003;Adigun, 2013;Badiora et al, 2016;Andresen et al, 2017;Abbas, 2018). For example, crime has been found to significantly increase with distance from the urban centres and with few exceptions decrease with population density while isolated rural settlements experience high crime rate compared to non-isolated urban settlements (Fafchamps and Moser, 2003;Adigun, 2013).…”
Section: Introductionmentioning
confidence: 99%